(3MhceI eQGbH GdMSGHGJ aj GdTQcGJ GdeSGgeI GdebjOI HGdHhQUI (B/ s - (3CMeO YGOd CHhRjOs; (3CMeO aGQhb hTGMjs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3JCJj CgejI GdHMK (B" (3MhceI eQGbH GdMSGHGJ aj GdTQcGJ GdebjOI HGdHhQUI (B" (3ef MjK chfg jhGLg OhQkG gGekG dCMO COhGJ GdQbGHI Ydi TQcGJ GdeSGgeI GdebjOI aj GdHhQUI, aef NdGd QbGHI eQGbH GdMSGHGJ, jJe EVaGA GdKbI Ydi GdHjGfGJ GdeGdjI ddTQcGJ GdeSGgeI GdebjOI aj GdHhQUI (B. (3CVa Edi Pdc, JJeKd CgejI GdHMK CjVkG ajeG jJYdb HHjGf MbjbjI OhQ eQGbH GdMSGHGJ hMOhO eSFhdjJg JLGg GdTQcI GdNGVYI dQbGHJg Ch JLGg eSGgejgG Ch JLGg GdZjQ ef LeghQ GdeSJajOjf ef GdbhGFe GdeGdjI ddTQcI ef OGFfjf heSJKeQjf hHfhc(B. (3hJe JbSje GdOQGSI Edi HGHjf QFjSjf jSHbge aUd JegjOj, MjK JfGhdJ GdOQGSI aj GdaUd GdJegjOj(B" (3eaghe MhceI GdTQcGJ heQGbH GdMSGHGJ aj TQcI GdeSGgeI (B" . (3CqeG Yf GdHGH GdChd ef gPg GdQSGdI, abO Med YfhGf (B" (3VhGHW GdMhceI GdNGUI HJOYje GSJbdGdjI eQGbH GdMSGHGJ (B"(3, HjfeG Med GdHGH GdKGfj ef gPg GdOQGSI YfhGf (B" (3GdeSFhdjI GdbGfhfjI deQGbH GdMSGHGJ (B" . (3hbO GfJgJ GdQSGdI HeLehYI ef GdfJGFL hGdJhUjGJ s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQjs
(3HHdjhLQGajG(B: (3UaMGJ (B289-306s
Keywords: (3GdJbQjQ GdSfhis; (3eYGjjQ eQGLYI GdMSGHGJs; (3GdeQcR GdbGfhfi deQGbH GdMSGHGJs; (3YbO GdeQGLYI s; (3OYhi GdTQcIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs